The Legal Concept of Truce - علي, محمد; بسام أحمد (Latakia University Journal - Economic and Legal Sciences Series, 2024)
ace Truce is the means of international law to enforce stopping military operations in land, sea and air between conflicting parties in order to create suitable circumstances to make peace process. But this does not necessarily mean achieving peace between the two parties. The truce may be continued according to the circumstances of the war and the will of the two parties. In this direction. The truce as a legal concept differs in its meaning from other terms in this concern such as :ceasefire, peace treaty and other terms such as the humanitarian truce is one of the effective means of international humanitarian law aimed at suspending the military operations in order to achieve humanitarian purposes such as: offering medical care for the wounded and burying the dead bodies for specific period of time in a specific geographical location without ending the state of war between the conflicting The United Nations' resolutions to enforce truce between conflicting parties are not obligatory according to the international law, but they represent a strong opinion of the majority of UN members in the General Assembly. However, truce can be imposed on parties by the United Nations Security Council resolutions under Chapter VII of the United Nations Charter if the parties are not committed to Security Council resolutions. It is important to distinguish between the truce agreements and the identification of states' borders. The legal concept of truce is temporal ceasefire for certain purposes, it is not concerned with the identification of borders which should be included in the international treaties.